2014
DOI: 10.2139/ssrn.2408496
|View full text |Cite
|
Sign up to set email alerts
|

Expressing Emotion and Fairness Crowding-Out in an Ultimatum Game with Incomplete Information

Abstract: Abstract:Recent experimental research has shown that when rating systems are available, buyers are more generous in accepting unfair offers made by sellers. It has also shown that sellers make fairer decisions when they are rated, while some studies show that they are little affected by the rating systems. These studies are conducted under complete information settings. However, asymmetric information about the values of traded commodities between sellers and buyers may change their perception of fairness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Recent research has found that democratic decision processes may raise people's pro-social behavior through a number of ways including the effects of signals sent through voting and the democracy premium (e.g., Dal Bó et al 2010, Tyran and Feld 2006, Kamei 2014. We could therefore expect that the presence of the endogenous process may drive their votes for the public good, assuming that some subjects have non-standard preferences and may enjoy a higher level of mutual cooperation when the public good regime is endogenously imposed.…”
Section: Results 6: Risk Attitudes By Treatment Prediction 3 Does Not mentioning
confidence: 99%
“…Recent research has found that democratic decision processes may raise people's pro-social behavior through a number of ways including the effects of signals sent through voting and the democracy premium (e.g., Dal Bó et al 2010, Tyran and Feld 2006, Kamei 2014. We could therefore expect that the presence of the endogenous process may drive their votes for the public good, assuming that some subjects have non-standard preferences and may enjoy a higher level of mutual cooperation when the public good regime is endogenously imposed.…”
Section: Results 6: Risk Attitudes By Treatment Prediction 3 Does Not mentioning
confidence: 99%